Stress and stiffness-based topology optimization of two-material thermal structures. (November 2021) - Tamijani, Ali Y.
Highlights: Simultaneous layout and compositional grading optimization. Incorporation of failure constraint and its sensitivity in the optimization scheme. Comparison of stiffness and strength-based designs for thermal and mechanical loads. Comparison of single-material and multi-material optimized designs performance. Abstract: Gradient additive manufacturing techniques are capable of implementing multiple materials with graded compositions into the fabrication of a single component. This provides a unique opportunity to control the properties of materials, such as thermal expansion, Young's modulus, and yield stress, and create a structure that otherwise would be infeasible. To utilize this capability, a density-based topology optimization framework is developed to optimize the spatial distribution of different materials, their interfaces, and the structural layout in order to enhance both the stiffness and the stress. Interpolation schemes to achieve these objectives are proposed, and the three levels of complexities, i.e., multi-material designs, design-dependent thermal loads, and stress constraints, are addressed. The framework is evaluated using three numerical examples, and the optimized stiffness and strength-based topology and material composition are demonstrated. Finally, the single-material and multi-material optimized designs are compared. The results show that the low compliance of the multi-material designs, while satisfying the failure constraint, was either infeasible or was achieved with a significantly higher weight for single-material structures.